An exploratory study of the use of electronic music technologies in clinical music therapy. - Magee WL; Burland K (Nordic Journal of Music Therapy, 2008)
In line with wider health and educational services, there is a growing demand for music therapists to apply electronic music technologies in clinical practice. Despite a handful of accounts indicating the benefits these tools offer, an objective assessment of their role in music therapy and guidelines for their application in therapy are lacking. A qualitative study collected data in semi-structured individual interviews from music therapists experienced in using electronic equipment using MIDI generated sounds triggered by specialist input devices. Interview transcripts were analyzed independently by two multidisciplinary investigators using open coding procedures from Grounded Theory, with member checking to enhance credibility. The findings propose a five-step treatment model when using technologies with people with complex needs. Accurate assessment of movement, positioning of the technology, and establishing the client's awareness of cause and effect are central to meeting clinical aims. Clinical indicators include complex physical and sensory disabilities, motivational problems, and specific needs pertaining to expression of identity. Their use is contraindicated in cases where it is known the client has no awareness of cause and effect.